Vegetation in fenced pastures - Milchunas, Daniel, photographer (Colorado State University. Libraries, 2007)
View of vegetation in and outside of exclosure fences on SGS, sm and lg mammal fences.
Keywords: experiments; grazing; SGS; shrublands; landscapes